The Novel Function of Nesfatin-1 as an Anti-inflammatory and Antiapoptotic Peptide in Subarachnoid Hemorrhage-Induced Oxidative Brain Damage in Rats - (:unkn) unknown (OXFORD UNIV PRESS INC, 2011)
BACKGROUND: There is substantial evidence to suggest that oxidative stress plays a significant role in the development of acute brain injury after subarachnoid hemorrhage (SAH). OBJECTIVE: To investigate the putative neuroprotective effect of nesfatin-1, a novel peptide with anorexigenic properties, in a rat model of SAH. METHODS: Male Wistar albino rats were randomly divided into control, saline-treated SAH, and nesfatin-1 (10 mu g/kg IP)-treated SAH groups. To induce SAH, rats were injected with 0.3 mL blood into their cisterna magna. Forty-eight hours after SAH induction, neurological examination scores were recorded and the rats were decapitated. Brain tissue samples were taken for the determination of blood-brain barrier (BBB) permeability, brain water content, and oxidative stress markers and for histological analysis. RESULTS: The neurological examination scores were increased on the second day of SAH induction. SAH resulted in impaired blood-brain barrier and edema, along with increased levels of brain tumor necrosis factor-alpha, interleukin-1 beta, interleukin-6, lipid peroxidation, protein carbonylation, and myeloperoxidase activity with concomitant decreases in antioxidant enzymes. Conversely, in the nesfatin-1-treated SAH group, SAH-induced neurological impairment and oxidative brain injury were ameliorated by nesfatin treatment. Furthermore, SAH-induced morphological changes in the basilar arteries were improved by nesfatin-1 treatment, whereas caspase-3 activity and SAH-induced elevations in the plasma levels of proinflammatory cytokines were also depressed by nesfatin-1 treatment. CONCLUSION: These findings suggest that nesfatin-1, which appears to have antiapoptotic and anti-inflammatory properties, exerts neuroprotection in SAH-induced injury in rats by inhibiting neutrophil infiltration and subsequent release of inflammatory mediators.
Keywords: Apoptosis; Nesfatin-1; Neutrophils; Oxidative stress; Subarachnoid hemorrhage; IMMUNOREACTIVITY; VASOSPASM; BARRIER; PERMEABILITY; INFLAMMATION; EXPRESSION; MORTALITY; NEURONS; INJURY; DYE